Building blocks of imagination - Jones, Christopher D. (HTS teologiese studies, 2023)
In the human context, the ubiquitous faculty of imagination is taken for granted. Whether we are singularly equipped with this ability or whether it is an evolved faculty also present in other life forms is a question that has been an issue ever since Darwin. A variety of research projects have indicated the presence of mental processes in non-human taxa and the faculty of imagination developed with increasing complexity over time, to its present status in humans. As an evolved faculty, encompassing a variety of non-humans, it serves as a useful tool to ascertain and understand the origins and unique quality of human mental processes, even to the extent of informing certain medical issues and problems in education. Several pointers exist that argue for human imagination as an evolved faculty that is shared within broad spectrum of taxa. Paleoanthropological research has provided insights as to the role of imagination in the early manifestations of religious behaviour in humans, the construction of effective stone tools by anatomically modern humans employing pyro technology, as well as their ability to mentally link ostensibly non-related natural phenomena like tidal fluctuations and the phases of the moon.Contribution: This review article explores imagination as an evolved faculty in an intersectional and interdisciplinary manner. This evolutionary reflection fits well with the purpose and inclusive nature of this special collection on the building blocks of our past, present and future.